Pedagogic competency management: Improving teacher performance in early childhood education programs - Suprihatin, Suprihatin (Universitas Islam Negeri Raden Intan Lampung, 2021)
Pedagogic competence is a fundamental competency in the framework of children's educational practices. Pedagogic competence is required as a system of knowledge about children's education that will become the basis or basis in children's educational practices and become the standard of success of children's educational practices. This research was conducted to analyze how pedagogic competence in improving the performance of PAUD teachers in the Gadingrejo Sub-district. The method used in this study is the qualitative research method by conducting observations, interviews, and documentation. The source of information is obtained through interviews with the head of the foundation, educators, and students. The results of research on pedagogic abilities of PAUD teachers in Qurotta Ayun and PAUD SPS Latifah Learning Group in organizing various aspects of child development according to age, designing child development activities according to age-based on curriculum, organizing educational development activities in children according to age, organizing and making assessment reports, evaluation of processes and evaluation of learning outcomes in children according to age, analyzing the theory of play according to aspects and stages of development, needs, potential talents and interests of children according to age, in general, is good enough. However, there needs to be an improvement in pedagogic management through the improvement of educational qualifications and competencies of educators through training activities, technical guidance, and workshops.